Respuesta :

Answer:

Option (D)

Step-by-step explanation:

In a function y shows the values of the function (Output values) and x shows the (input values).

Therefore, to convert any equation into the function, we will solve the equation for y.

Given equation is,

680x + 10y - 1000 = 0

680x + 10y = 1000

68x + y = 100

y = -68x + 100

Now replace y by f(x).

Therefore, the function will be,

f(x) = -68x + 100

Option (C) will be the correct option.

Answer:

f(x) = -68x + 100

Step-by-step explanation:

Otras preguntas

ACCESS MORE